Retrofitting a Building's Envelope: Sustainability Performance of ETICS with ICB or EPS - Silvestre, José D. (2019)
This paper analyses the environmental, energy, and economic performances of the External Thermal Insulation Composite System (ETICS) using agglomerated insulation cork board (ICB) or expanded polystyrene (EPS) as insulation material applied in the energetic renovation of the building envelope during a 50-year study period. A comparison between ETICS using ICB and EPS, for the same time horizon, is also presented. The environmental balance is based on “Cradle to Cradle” (C2C) Life Cycle Assessment (LCA), focusing on the carbon footprint and consumption of nonrenewable primary energy (PE-NRe). The characteristics of these products in terms of thermal insulation, the increased energy performance provided by their installation for retrofit of the buildings’ envelope, and the resulting energy savings are considered in the energy balance. The estimation of the C2C carbon and PE-NRe saved is considered in the final balance between the energy and environmental performances. ETICS with ICB is environmentally advantageous both in terms of carbon footprint and of PE-NRe. In fact, the production stage of ICB is less polluting, while EPS requires lower energy consumption to fulfil the heating and cooling needs of a flat, due to its lower U-Value, and its lower acquisition cost results in a lower C2C cost. Comparing both ETICS’ alternatives with reference solutions, it was found that the latter only perform better in the economic dimension, and only for an energy consumption to fulfill less than 25% of the heating and cooling needs. This paper represents an advance to the current state-of-the-art by including all the life-cycle stages and dimensions of the LCA in the analysis of solutions for energy renovation of building envelopes